2019
DOI: 10.3390/cryst10010002
|View full text |Cite
|
Sign up to set email alerts
|

The Photothermal Stability Study of Quantum Dots Embedded in Sodium Chlorides

Abstract: An efficient and useful method for the incorporation of colloidal quantum dots (QDs) into ionic matrices is demonstrated. We prepared three different synthesis methods, which are traditional saturated-salt water, methanol-assisted, and ethanol-assisted methods. The continuous thermal and photonic stress tests indicate that the high temperature, instead of photonic excitation stress, is more detrimental to the illumination capability of the quantum dots. While the traditional saturated-salt water synthesis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Based on the developed methods to embed QDs into ionic macromatrices, detailed studies have been carried out to investigate the effects of the ionic matrices on the properties of the incorporated QDs. In order to understand the difference among methods, Huang and his co-workers investigated the photostability of CdTe QDs embedded in the same NaCl matrix using three different methods, 65 comparing slow evaporation in water to methanol assisted LLDC and ethanol assisted LLDC methods. From this, it has been found that the CdTe QDs loaded via the slow evaporation and methanol assisted LLDC methods revealed higher photostability than that of the CdTe QDs sealed using the ethanol assisted LLDC method (Fig.…”
Section: Properties Of Np Loaded Inorganic Macrocrystalsmentioning
confidence: 99%
“…Based on the developed methods to embed QDs into ionic macromatrices, detailed studies have been carried out to investigate the effects of the ionic matrices on the properties of the incorporated QDs. In order to understand the difference among methods, Huang and his co-workers investigated the photostability of CdTe QDs embedded in the same NaCl matrix using three different methods, 65 comparing slow evaporation in water to methanol assisted LLDC and ethanol assisted LLDC methods. From this, it has been found that the CdTe QDs loaded via the slow evaporation and methanol assisted LLDC methods revealed higher photostability than that of the CdTe QDs sealed using the ethanol assisted LLDC method (Fig.…”
Section: Properties Of Np Loaded Inorganic Macrocrystalsmentioning
confidence: 99%